Geographic access to hospice care for children with cancer in Tennessee, 2009 to 2011 - Lindley, Lisa C. (Am J Hosp Palliat Care, 2014)
The geographic interface between the need for and the supply of pediatric hospice may be critical in whether children with cancer access care. This study sought to describe the geographic distribution of pediatric hospice need and supply and identify areas lacking pediatric hospice care in Tennessee over a 3 year time period. Using ArcGIS, a series of maps were created. There was a consistent need for care among children with cancer across the state. Most urban areas were supplied by pediatric hospices, except the Knoxville area. Areas within the state were identified where the supply of pediatric hospice care declined, while the need for hospice care was unchanging. This study has important regulatory implications for clinicians practicing in Certificate of Need states such as Tennessee.